Continuous Stirred Tank Reactor Application for Renewable Methane from Anaerobic Biodegradation of Petrochemical Wastewater - Siddique, Md. Nurul Islam; Zularisam, A. W. (UM Press, 2012)
Anaerobic digestion using continuous stirred tank reactor (CSTR) as a potentially sustainable technology for petrochemical waste water treatment was investigated by strategic raise in organic loading rate (OLR). The reactor efficiency was observed at 4 to 2d hydraulic retention time (HRT) with OLR 7 to 11 g-COD/Ld. Startup operation of CSTR was closely examined up to 60 days. Masophilic performance of CSTR was studied. Results enclosed that highest COD elimination efficiency was 98±0.5% at 7.5 g-COD/Ld OLR and 4d HRT. Maximum biogas and methane production were 0.80 L/g-CODremoved d and 0.60 L/g-CODremoved d respectively, comprising average methane of 65.49%. The complete acclimatization took place at 37 ˚C with great process stability. The current work specifies methane productivity of petrochemical waste water under masophilic temperature.